Conceptualization and Scope of Emergent Drugs in Full Progression in this Century - Barrabeitg, Gabriel Lajús (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
The world of the drugs is in constant growth and transformation. They incorporate to those that have existed from remote times, more and new, but even more dangerous and more addictive, and simultaneously multiple and new concepts are formulated that hinder its demarcation and learning. Objectives: To debate the precision of the main concepts on emergent or equivalent drugs, emitted in the last 10 years and, to contain novel aspects of the reach. Material and methods: It was made during the first semester of 2017, in Havana, Cuba, an orderly revision of information related with the concepts on emergent drugs and their reach, by means of electronic searches in libraries of magazines national doctors and indexed foreigners, as well as in texts, in the last 10 years. Development: When subjecting to the analysis these concepts, it was appreciated that they were restricted and imprecise that didn't pay to the prevention and that could generate until confusion. One kept in mind the reach of the novelty of these substances, and when paying attention to the great quantity of compounds that were not contemplated in precedent definitions, it was emitted, for the author with integrative premeditation, one new. onclusions: Drugs growth that circulate in this Century has been so dynamic, enormous, precipitate and excessively quickly, diverse for origin, composition and geographical unequal distribution that have been hindered its conceptualization, where the new, its reach, turns drugs riskier and unknowns, also invasive and additives, that allowed to contribute a comprehensive as a new whole concept.